Factors associated with incomplete colonoscopy in symptomatic patients scheduled for elective colonoscopy - Mohamad, Abdul Malek; Elagili, Faisal; Md Nor, Azmi; Jaafar, Khairul Azhar; Sainal, Mohd. Yusof; Mohammad Aidid, Edre (Wiley-Blackwell Publishing Ltd, 2021)
Aim: For endoscopists, the caecal intubation rate (CIR) is an important quality standard1. However, previous studies have shown that patients who had a colonoscopy due to symptoms had a lower CIR than those who had a screening colonoscopy; additionally, symptoms were found to be one of the predictors of incomplete colonoscopy.. There is a scarcity of information on the factors associated with incomplete colonoscopies in patients who have symptoms. The purpose of this study was to look at the factors that were linked to incomplete colonoscopies in patients who had symptoms. Method: A single-center, prospective, observational study was conducted, and all symptomatic patients undergoing colonoscopy between November 2019 and March 2021 were included. The significant risk factors for incomplete colonoscopy were evaluated by using a multiple logistic regression model. Results: Two hundred and seven patients (59% male) with a mean age of 63 ± 21 years. Indications include bleeding (45%), bowel habit change (30%), pain (21%), and miscellaneous (4%). The rate of caeca intubation was 77%. The results of multivariate logistic regression analysis revealed three factors that were significantly associated with an increased risk of incomplete colonoscopy: previous abdominal or pelvic surgery(odds ratio [OR] 2.99; confidence interval [CI] 1.07 to 8.35, P = 0.036), severe pain score during the procedure(odds ratio [OR] 19.56; confidence interval [CI] 6.06 to 63.13, P < 0.001) and poor bowel cleansing (odds ratio [OR] 7.94; confidence interval [CI] 2.82 to 22.38, P < 0.001). Conclusion: In this study, Colonoscopy in symptomatic patients results in lower cecal intubation rates. The only two modifiable patient-related predictors influencing cecal intubation were the quality of bowel preparation and severe pain during the procedure